Ludic use in science teaching: didactic game on atmospheric chemistry - Caroline Medeiros Martins de Almeida; Tania Renata Prochnow; Paulo Tadeu Campos Lopes (Universidad Distrital Francisco José de Caldas, 2016)
Science education ispermeated by abstract scientific content and complex to students understanding. Then comes the need of the teacher teach lessons more interesting and motivating, seeking alternatives to provide learning experiences that are more contemporary and assimilable for students. This study aimed to analysing how the use of an educational game can help in Science teaching and learning process, in the content of atmospheric chemistry, for the 9th year of elementary school. We also found the opinion of students regarding the proposed activity. Comparing the responses of the tests, we noticed a greater apprehension of the content in the post-test period, showing that the methodology helped in learning of the atmospheric chemistry concepts, even if some students have not fully achieved the objectives.